Notaris dan Akibat Pembatalan Akta Jual Beli Saham Silang (Cross Holding) oleh Pengadilan - Dwi Tiara Febrina; Benny Djaja; Maman Sudirman (UNES Law Review, 2023)
This research aims to interpret the legal consequences for Notaries regarding the Cross Holding Deed of Sale and Purchase of Shares which annulled by the Court used by a normative juridical approach, by examining library materials including statutory regulations, legal rules, legal principles and analyzing the provisions of statutory regulation, court decision and other legal material. The public views that notaries always know all matters relating to law, so notaries are expected to be able to inform and explain in detail to their clients that the deed to be made contains prohibited reasons. Even though at the time the deed was drawn up, the Limited Liability Company Law didn’t contain a prohibition on cross share ownership, the prohibition on cross share ownership was stated in the Law on the Prohibition of Monopoly Practices and Unfair Business Competition. In this case the applicant did not involve a third party, the Notary who made the Deed of Cross Share Sale and Purchase. However, a Notary in carry out his position as a public official must apply the principle of prudence, so that in carry out his duties as a Notary doesn’t cause harm to his clients and does not create legal uncertainty.